2007
DOI: 10.1016/j.ejphar.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Lobelane decreases methamphetamine self-administration in rats

Abstract: Lobelane, a minor alkaloid of Lobelia inflata and a synthetic, des-oxy analog of lobeline, has good affinity for the vesicular monoamine transporter and the dopamine transporter. The current study examined the ability of lobelane to specifically decrease methamphetamine self-administration. Rats were trained on a fixed ratio 5 schedule of reinforcement to self-administer methamphetamine (0.05 mg/kg/infusion, i.v.) or to respond for sucrose pellets. Upon reaching stable responding, rats were pretreated with lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 15 publications
4
78
0
Order By: Relevance
“…Through an interaction with VMAT2, lobeline inhibits the neurochemical and behavioral effects of methamphetamine (Teng et al, 1997(Teng et al, , 1998Harrod et al, 2001;Miller et al, 2001;Dwoskin and Crooks, 2002;Nickell et al, 2010). Lobelane, a lobeline analog with greater selectivity for VMAT2, decreased both methamphetamineevoked DA release (IC 50 ϭ 0.65 M; I max ϭ 73.2%; same experimental conditions as the current work) and methamphetamine self-administration (Zheng et al, 2005a;Neugebauer et al, 2007;Beckmann et al, 2010;Nickell et al, 2010Nickell et al, , 2011. Unfortunately, further development of lobelane as an effective pharmacotherapy was hindered by unacceptable drug-likeness properties.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Through an interaction with VMAT2, lobeline inhibits the neurochemical and behavioral effects of methamphetamine (Teng et al, 1997(Teng et al, , 1998Harrod et al, 2001;Miller et al, 2001;Dwoskin and Crooks, 2002;Nickell et al, 2010). Lobelane, a lobeline analog with greater selectivity for VMAT2, decreased both methamphetamineevoked DA release (IC 50 ϭ 0.65 M; I max ϭ 73.2%; same experimental conditions as the current work) and methamphetamine self-administration (Zheng et al, 2005a;Neugebauer et al, 2007;Beckmann et al, 2010;Nickell et al, 2010Nickell et al, , 2011. Unfortunately, further development of lobelane as an effective pharmacotherapy was hindered by unacceptable drug-likeness properties.…”
Section: Discussionmentioning
confidence: 62%
“…1), a chemically defunctionalized, saturated analog of lobeline, competitively inhibited DA uptake at VMAT2 and exhibited increased affinity and selectivity for VMAT2 compared with lobeline (Miller et al, 2001;. Lobelane inhibited methamphetamine-evoked DA release and decreased methamphetamine self-administration; however, tolerance developed to the latter behavior effects (Neugebauer et al, 2007;Nickell et al, 2010). Unfortunately, lobelane exhibits decreased water solubility and diminished drug-likeness properties caused by its decreased polarity resulting from removal of the keto and hydroxyl functionalities of lobeline.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that removal of the oxygen-containing functional groups of lobeline, such as with lobelane, diminished affinity for [ 3 H]nicotine and [ 3 H]methyllycaconitine binding sites (␣4␤2* and ␣7* nAChRs, respectively, where * indicates the putative nAChR subtype assignment) (Miller et al, 2004) and retained affinity for VMAT2 at the [ 3 H]DTBZ binding site on VMAT2 (Zheng et al, 2005a). Furthermore, lobelane retained the ability to decrease methamphetamine self-administration (Neugebauer et al, 2007). Thus, the findings that methamphetamine interacts with VMAT2 to increase extracellular DA and ultimately methamphetamine-induced reward, the selective interaction of lobelane with VMAT2, and the observations that lobelane inhibits the effects of methamphetamine provide support for VMAT2 as a pharmacological target for the development of novel treatments for methamphetamine abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral experiments were conducted as described previously (Neugebauer et al, 2007). Operant conditioning chambers (ENV-008; MED Associates, St. Albans, VT) were enclosed within sound-attenuating compartments (ENV-018M; MED Associates).…”
Section: Introductionmentioning
confidence: 99%